24‐4: Flexible AMOLED based on Oxide TFT with High Mobility. Issue 1 (May 2017) - Wang, Lei; Ruan, Chongpeng; Xu, Hua; Le, Min; Zou, Jianhua; Tao, Hong; Zhou, Lei; Pang, Jiawei; Lan, Linfeng; Ning, Honglong; Wu, Weijing; Yao, Rihui; et al.
Abstract : We report a high performance foldable and rollable AMOLED display with 300 ppi (real RGB) driven by oxide thin film transistors (TFTs) based on a polyimide (PI) substrate. No new defects appear on the display after 100, 000 times bending with radius of curvature at 3 mm. In the oxide TFT, the Lanthanide rare earth doped In‐Zn‐O (LnIZO) is employed as the key active layer to improve the mobility and stability. The fabricated Ln‐IZO TFT with BCE process exhibits a high field‐effect mobility of 40 cm 2 V ‐1 s ‐1, a subthreshold swing of 0.13 V/decade, and an Ion /Ioff ratio of 10 9 . Meanwhile, laminated Al2 O3 /MgO film prepared by the method of atomic layer deposition (ALD) is used as the encapsulation of AMOLED display.